1985
DOI: 10.1007/bf00291069
|View full text |Cite
|
Sign up to set email alerts
|

Sulphonylurea therapy doubles B-cell response to glucose in Type 2 diabetic patients

Abstract: Summary. The effect of sulphonylurea therapy for 3 weeks on glucose-stimulated insulin secretion and insulin resistance was studied in Type 2 diabetic patients. The fasting plasma insulin and C-peptide concentrations on diet alone were compared with each subject's fasting concentrations on sulphonylurea treatment at a lower fasting plasma glucose and at the original diet-alone glycaemic level obtained by the hyperglycaemic clamp technique. At this isoglycaemic level (mean 11 mmol/1), plasma insulin levels incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 36 publications
4
23
0
1
Order By: Relevance
“…While an inhibitory effect may lead to an underestimation of the secretory responses, the same insulin infusion rates were used in both the placebo and treatment arms in the current study and so would not be expected to affect the comparison between them. Moreover, the degree of pancreatic stimulation seen in our study was similar to that seen in other studies [19,20]. Sulfonylureas are recognised as being associated with hypoglycaemia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While an inhibitory effect may lead to an underestimation of the secretory responses, the same insulin infusion rates were used in both the placebo and treatment arms in the current study and so would not be expected to affect the comparison between them. Moreover, the degree of pancreatic stimulation seen in our study was similar to that seen in other studies [19,20]. Sulfonylureas are recognised as being associated with hypoglycaemia.…”
Section: Discussionsupporting
confidence: 92%
“…Hosker et al investigated the effect of glibenclamide and chlorpropamide on insulin secretion at a plasma glucose of 11 and 13 mmol/l and found an approximate doubling of insulin secretion at each of these concentrations, closely matching the results we have shown here [19]. Groop et al showed a tendency for an additive effect on second phase insulin secretion in patients with type 2 diabetes at glucose levels ranging from 10 to 25 mmol/l [20].…”
Section: Discussionsupporting
confidence: 86%
“…Sulphonylurea therapy improves beta-cell function approximately twofold [2], but the marked insulin secretory defect persists in most patients, so that the enhancement is usually insufficient to maintain near-normal glucose concentrations, Diabetologia (1997) 40: 205-211 Near-normalisation of diurnal glucose concentrations by continuous administration of glucagon-like peptide-1 (GLP-1) in subjects with NIDDM Summary The gut hormone, glucagon-like peptide-1 (GLP-1) is a potent insulin secretogogue with potential as a therapy for non-insulin-dependent diabetes mellitus (NIDDM). GLP-1 has been shown to reduce glucose concentrations, both basally, and, independently, in response to a single meal.…”
mentioning
confidence: 99%
“…' We chose to study glibenclamide as it was the most commonly used sulfonylurea agent at the time, and because its principal mechanism of action on the pancreatic beta cell, namely to inhibit the sulfonylurea receptor (SUR)/inward rectifying potassium (KiR6.2) channel to depolarise the cell, is shared by the sulfonylurea class as a whole [3]. Similar results have been shown with other members of the class, such as gliclazide, in hyperglycaemic conditions [4]. In clinical practice, glibenclamide is well known to be particularly prone to cause hypoglycaemia and has pharmacokinetic and pharmacodynamic properties that are likely to underlie this.…”
Section: Secretion Sulfonylureamentioning
confidence: 93%